Development and Evaluation of a Computer-Aided Speech-to-Print Transcription System. Final Report - National Technical Inst. for the Deaf, Rochester, NY.; National Technical Inst. for the Deaf, Rochester, NY. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 2000)
This final report describes the development and evaluation of C-Print, a system for transcription of computer-aided speech to print. Chapter 1 is an introduction to the 3-year federally supported project. Chapter 2 provides background information on current speech-to-print systems. Chapter 3 focuses on needed improvements in C-Print, especially improvements in the general and specialized dictionaries and development of procedures for condensing text. Chapter 4 focuses on the C-Print captionist, including roles and responsibilities, training procedures, the training workshop, and the workshop evaluation. Chapter 5 discusses C-Print captionists' perceptions of their experiences in supporting students in the classroom. Chapter 6 reports on a questionnaire and in-depth interview studies of the system with 36 deaf or hard of hearing students at the college level. The final chapter reports on a pilot study using C-Print with two deaf high school students. An appendix lists other materials providing information on the C-Print Project. (Contains 31 references.) (DB)
Sponsoring Agency: Special Education Programs (ED/OSERS), Washington, DC.
Contract Number: 180J3011.
ERIC Note: Project director was Michael S. Stinson. Co-principal investigator was Barbara G. McKee.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Accessibility (for Disabled); Captions; College Students; Computer Software; Computer Uses in Education; Deafness; Demonstration Programs; Hearing Impairments; High Schools; Higher Education; Paraprofessional Personnel; Pilot Projects; Research and Development; Training Methods; Reports, Descriptive; Reports, Research